Increasing eccentric contraction duration enhances resistance exercise‐induced inhibitory control improvement while reducing the exertion perception: A pilot study in young men - Kento Dora; Takeshi Hashimoto; I. Wayan Yuuki; Su Yang; Kousei Tachi; Kaito Hashimoto; Shumpei Fujie; Motoyuki Iemitsu; Shigehiko Ogoh (Physiological Reports)
Abstract Low‐intensity resistance exercise with slow movement and tonic force generation (LRST) effectively improves cognitive inhibitory control (IC) while heightening the subjective perception, which is a barrier to exercise adherence. Compared with concentric (CON) contractions, eccentric (ECC) contractions have greater brain activation related to cognitive functions while decreasing subjective perception. Therefore, we examined whether LRST with a longer duration of ECC contraction (ECC‐LRST) could further enhance exercise‐induced IC improvement while reducing the subjective perception, compared with traditional LRST. Fourteen healthy, young males performed both ECC‐LRST and LRST, with 30% of their one‐repetition maximum. The subjective perceptions of exertion and pain associated with exercise were assessed. IC was evaluated at baseline, immediately post‐exercise, and 15‐min post‐exercise. IC improved immediately after both ECC‐LRST and LRST (both Ps < 0.05). However, the improvement in IC persisted until 15 min post‐exercise for ECC‐LRST compared with baseline (p = 0.031) but not for LRST, which showed a significantly smaller improvement than ECC‐LRST (p = 0.042). A lower perceived pain (p = 0.039) and a trend toward a lower perceived exertion (p = 0.078) were observed during ECC‐LRST than during LRST. ECC‐LRST is an effective resistance exercise protocol for improving IC while reducing the perception of exertion.